The harmonica - Johnston, Tony 1942- Mitwirkender; Mazellan, Ron Mitwirkender (Charlesbridge, 2004)
"The Harmonica" was inspired by a true story. Henryk Rosmaryn grew up in Czeladz, Poland. In 1939 the Germans invaded his homeland. Henryk was taken to Dyhernfurt concentration camp where, with the help of the harmonica that his father had taught him to play, he survived the hardsship and sorrow of that prison. After the war he came to the United States and chanched his name to Henri Rosmarin. Again with the aid of his harmonica, he shared his wartime experience with others, especially teenagers, in the hope that they might bring abaout a better future. Although he died in 2001, his is an ongoing story of the power of music and the strength of the human heart.